Em nome de Deus, amém!: mulheres, escravos, famílias e heranças através dos testamentos em Belém do Grão-Pará na primeira metade do século XIX - PASTANA, Andréa da Silva (Universidade Federal do Pará, 2013)
The present dissertation is intended to investigate the strategies of women, slaves, former slaves and free men, considering the configuration of patrimony and home maintenance, in view of the distribution of goods in the city of Belém do Grão Pará (Belém of the Great Pará), in the first half of the 19th century and 2 thus, to perceive women and slave‟s spaces, roles and duties for the sake of good‟s inheritance, by means of wills (testaments) made during the 1800-1850 period. Women, who were charged of managing a home, would essentially perform a man‟s function, and they were the only ones who provided for the family‟s economy and ‘education at home. Other focus of the analysis refers to the presence of the captives on the wills (testaments), which is something to be considered, when it comes to drawing an outline of the slaves‟ economic and social value. It‟s also of major importance to understand the various ways slaves were used by their masters in the preparation of the will. Thus, an effort is made to elucidate the criteria employed for the description of the goods (slaves), with some focus on the liberty concessions made by means of the wills. It‟s equally relevant to approach the dynamics involving men and women during their will‟s making process. This study gives way to a reverberation over the routine of Belém do Grão Para‟s inhabitants, and their final arrangements during the act of making a will.